Dielectric RF resonators with open boundaries for studying radiation effect on electrodynamic characteristics of solid dielectrics - Kushnir, V.A.; Kramarenko, K.Yu.; Mytrochenko, V.V.; Nikitina, O.D.; Perezhogin, S.A.; Selivanov, L.I. (Вопросы атомной науки и техники, 2020)
The use of dielectric materials in the charged particles accelerators requires investigation of changes in the electrodynamic properties of these materials under the influence of ionizing radiation. First of all it is necessary to study the effect of radiation on the complex dielectric permittivity (ε and tgδ) of these materials. The actual task is to measure very small relative changes in the dielectric constant, for example, Δε/ε∼10⁻⁴. Such accuracy can be provided by resonator methods. In the present work results of theoretical and experimental research of microwave dielectric resonators with open boundaries are given. It is shown, that they can be used to measure dielectrics during irradiation by gamma radiation or charged particles beam. The analysis of factors that affect the accuracy of measurements is carried out. Використання діелектричних матеріалів у прискорювачах заряджених частинок вимагає дослідження зміни електродинамічних властивостей цих матеріалів під дією іонізуючого випромінювання. В першу чергу необхідно вивчити вплив випромінювання на комплексну діелектричну проникність (ε and tgδ) цих матеріалів. Актуальним завданням є вимір малих відносних змін діелектричної проникності, наприклад, Δε/ε∼10⁻⁴. Така точність може бути забезпечена резонаторними методами. Наведено результати теоретичних та експериме-нтальних досліджень НВЧ-діелектричних резонаторів з відкритими границями. Показано, що вони можуть бути використані для вимірювання параметрів діелектриків при опроміненні гамма-випромінюванням або пучком заряджених частинок. Проведено аналіз факторів, що впливають на точність вимірювань. Использование диэлектрических материалов в ускорителях заряженных частиц требует исследования изменения электродинамических свойств этих материалов под действием ионизирующего излучения. В первую очередь необходимо изучить влияние излучения на комплексную диэлектрическую проницаемость (ε and tgδ) этих материалов. Актуальной задачей является измерение малых относительных изменений диэлек-трической проницаемости, например, Δε/ε∼10⁻⁴. Такая точность может быть обеспечена резонаторными методами. Приведены результаты теоретических и экспериментальных исследований СВЧ-диэлектрических резонаторов с открытыми границами. Показано, что они могут быть использованы для измерения парамет-ров диэлектриков при облучении гамма-излучением или пучком заряженных частиц. Проведен анализ фак-торов, влияющих на точность измерений.